Improving students’ comprehension on the theory of law (nazariyyah al-hukm) through action research - Kayadibi, Saim (University of Malaya, 2011)

(untitled)
In recent years, it is being observed that the medium of instruction in the Academy of Islamic Studies has moved from the strictly local language to a multi-lingual education system that includes Arabic and English beside Malay. With a considerable rise of the rank of the University of Malaya at the ladder of the world academic ranking, the academy has introduced serious developments similar as in other faculties of the University. The curriculum has been developed and turned into an international form as well as the staffs have been employed preferably according to these changes. Imparting instruction of the courses in different foreign languages at the academy, brought at the beginning initial reactions and difficulties. The students could not fully understand the subject matter of the courses; and there were communication gaps between teachers and students. Moreover, the students faced difficulties during the preparation and taking of exams because they had to read sources in foreign languages other than their native language. Imparting instruction and learning, especially of the law subjects in their original languages such as Arabic and English, is considered a major achievement for both students and the academy. The investigation of the role of language in teacher education is highly significant for further developments.Therefore this paper attempts to investigate the role played by the teacher/lecturer in the comprehension of the subject of the theory of law (Nazariyyah al-Hukm) in the multi-cultural environment in order to achieve maximum benefit; how the diversity of languages could be turned into an opportunity to enhance both teachers’ and students’ achievement.